16 HOURS PHOTOPERIOD IN HOLSTEIN HEIFERS IN THE SUBTROPICS: EFFECTS IN DEVELOPMENT AND AGE TO FIRST ESTRUS - Valenzuela-Jiménez, Nicolás; Rodríguez-Hernández, Karla; Hernández-Cerón, Joel; Vera-Ávila, Héctor; Núñez-Hernández, Gregorio; Villa-Godoy, Alejandro (Ecosistemas y Recursos Agropecuarios, 2015)
Both growth and milk production in heifer calves are stimulated by a long photoperiod, though this has not been proven yet in subtropical areas. To evaluate the effect of 16 hr of light (L16) on calves suckling (LAC) and/or pre-pubertal stages (PP) in a subtropical area, 325 calves (36 ± 0.4 kg) were randomized into two groups: L16 or natural photoperiod (LNAT). At seven months of age, 198 of these calves (195 ± 2 kg) were randomly assigned to L16 or LNAT. The following were determined at the beginning and end of LAC and PP stages: Weight (PC, kg), height (AC, cm), thickness of back-fat (GG, cm) and of Longissimus dorsi (LD, cm); pelvic area (AP, cm2), body condition (CC), age at first estrus, mammary gland depth (PGM, cm) and width (AGM, cm). The statistical analysis was made using ANOVA for a 2 X 2 factorial arrangement. At the end of LAC, GG was lower and LD greater in L16 animals, while, at the end of PP, L16 heifer calves had a greater PC (260 ± 3 vs 250 ± 3), AP (166 ± 1.2 vs 153 ± 1.2), LD (3.18 ± 0.04 vs 2.90 ± 0.04), and AGM (2.41 ± 0.02 vs 2.21 ± 0.02), but a lower GG (0.114 ± 0.003 vs 0.139 ± 0.003) as compared to LNAT heifer calves. More L16 animals (67 %) presented estrus versus LNAT (38 %)
Keywords: Photoperiod; development; heifers calvez; estrus; subtropical